Changes in resting heart rate variability across the menstrual cycle. (18th June 2014) - Tenan, Matthew S.; Brothers, R. Matthew; Tweedell, Andrew J.; Hackney, Anthony C.; Griffin, Lisa
Abstract Heart rate variability (HRV) is a noninvasive indicator of autonomic control. This study examines HRV changes across a normal menstrual cycle and proposes a novel piecewise function controlling for the effects of breathing on HRV spectral parameters. A resting ECG was collected from 13 women at five points in their menstrual cycle. Both heart rate and breathing rate increased across the cycle (p < .01) while time‐domain variability decreased (p = .04). Use of the piecewise function for breathing rate in HRV spectral analysis was confirmed by a substantial increase in model goodness‐of‐fit. HRV spectral parameters, controlled for breathing with the piecewise function, confirm that the decrease in variability is likely due to a parasympathetic withdrawal, since high frequency HRV decreases (p = .02).